(untitled) (Revista Contexto & Saúde, 2026)
Multicomponent exercise training is considered a form of general training that can help fight harmful aging processes, leading to improved functional ability. This review therefore sought to investigate the effects of multicomponent exercise training on the functional performance of healthy older adults. Two independent reviewers conducted the data search and extraction as well as the risk-of-bias analysis. Randomized clinical trials comparing the effects of multicomponent exercise training with the effects of another exercise intervention or no exercise in a control group in healthy individuals aged 60 years or older were included. A systematic search of the literature was carried out in the following databases: PubMed, PEDro, CINAHL and Embase. The risk of bias was assessed with the Risk of Bias 2 tool. A total of 19 studies were included in the qualitative synthesis. Most of the studies were considered to give rise to “some concerns” in terms of risk-of-bias. The quality of evidence and the strength of recommendations were evaluated using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. The quality of evidence was rated as low for both functional capacity and functional performance, and very low for all other outcomes. The results of the meta-analysis showed that participants who underwent multicomponent exercise training had a better functional-performance outcome as measured by the timed up-and-go, gait-speed and 30-second sit-to-stand tests as well as the Short Physical Performance Battery. An improvement in functional ability as measured by the 6-minute walk test was observed. In healthy older adults, twice-weekly MCET can improve functional performance, especially when combining aerobic, strength, and other exercises at moderate intensity. However, the evidence is limited, and further well-designed studies with larger samples are needed.